Financing of NCD Prevention in LMICs: Belarus Case Study - Ammar Rashid; Kassim Nishtar; Saba Amjad; Huma Tahir (Journal of the Pakistan Medical Association, 2026)
Objective: To estimate spending on NCD prevention in Jamaica and identify the enablers, challenges and dynamics underpinning population-level NCD prevention spending, with particular focus on tobacco use, harmful use of alcohol, unhealthy diets and physical inactivity. Methods: Primary and secondary data collection was used to examine processes and organizational contexts that shape the formulation of policy and financial frameworks for NCD prevention. The methodology was categorized into three tiers; an academic literature review, scrutiny and analysis of official policy documents and budgetary data on health and NCDs, and in-depth stakeholder interviews with key government officials leading NCD programmes. Government and government-routed donor spending on population level prevention was gauged to estimate NCD prevention spending. Where possible, impact of prevention programmes on disease incidence and risk factors was gauged through available outcome indicators. Results: From 2016 to 2020, Belarus allocated an estimated BYN 15,762,041 to population level NCD prevention, which amounts to about 6.6% of the NCD-related budget and 0.02% of the total state health budget. Despite being among highest spenders in the world on health and shifting policy towards NCDs in recent years, allocations for NCD prevention remain low. Recent enablers include progress on taxing and reducing use of tobacco and alcohol and high levels of political commitment to health. Challenges include excess allocations towards curative infrastructure and services, focus on specialist instead of preventive primary care, inadequate focus on rising obesity and salt consumption, limited health communication and low population participation in health care. Conclusion: Belarus has increased focus on NCDs and risk factors in recent years, but this is not reflected yet in spending priorities. Re-routing its considerable health spending toward NCD prevention programmes could both mitigate its growing NCD disease burden and bring significant economic benefits. Keywords: Non-communicable, Diseases, Tobacco, Incidence, Illness